(untitled) (Bangladesh Journal of Livestock Research, 2022)
Goats and sheep have the capacity to provide meat, milk, leather, and wool, making them valuable assets for the global livestock business, particularly in Southeast Asia, the Mediterranean region, and African nations. Respiratory diseases are the primary cause of death for these animals, accounting for about half of their deaths. Whatever their causes, goat and sheep infectious respiratory diseases account for 5.6% of all small ruminant diseases and disorders. Most of these have an infectious origin, particularly those that are bacterial, parasitic, fungal, or viral. PPR, caprine arthritis encephalitis, and bluetongue are the main viruses that cause respiratory diseases in goats. Through the use of a roadmap, the World Organization for Animal Health (WOAH) has established a global strategy for the eradication of PPR from the planet by 2030. Conversely, the two main bacterial causes of respiratory diseases are Pasteurella and Mycoplasma species, which can co-infect viral disorders or act as the primary cause. They can also exacerbate existing infections and lead to incorrect diagnoses. Numerous surveillances identified fungal infections, particularly Aspergillosis and Conidiobolomycosis, as well as parasite infections such as nasal myiasis and verminous pneumonia. In the review paper, we provide the most recent updated results on such diseases and their causative agents, taking into account elements such as distribution, transmission, spatiotemporal dynamics, possible risk factors, clinical signs and symptoms, treatment, avoidance, and control methods. Lastly, we offer some particular suggestions for addressing the respiratory conditions that affect goats. Bang. J. Livs. Res. Vol. 29 (1&2), 2022: P. 1-20